Decision Making in Patients With Metastatic Spine. The Role of Minimally Invasive Treatment Modalities - Conti, Alfredo; Acker, Güliz; Kluge, Anne; Loebel, Franziska; Kreimeier, Anita; Budach, Volker; Vajkoczy, Peter; Ghetti, Ilaria; Germano', Antonino F.; Senger, Carolin (Frontiers in Oncology, 2019)
Spine metastases affect more than 70% of terminal cancer patients that eventually suffer from severe pain and neurological symptoms. Nevertheless, in the overwhelming majority of the cases, a spinal metastasis represents just one location of a diffuse systemic disease. Therefore, the best practice for treatment of spinal metastases depends on many different aspects of an oncological disease, including the assessment of neurological status, pain, location and dissemination of the disease as well as the ability to predict the risk of disease progression with neurological worsening, benefits and risks associated to treatment and, eventually, expected survival. To address this need for a framework and algorithm that takes all aspects of care into consideration, we reviewed available evidence on the multidisciplinary management of spinal metastases. According to the latest evidence, the use of stereotactic radiosurgery (SRS) or stereotactic body radiotherapy (SBRT) for spinal metastatic disease is rapidly increasing. Indeed, aggressive surgical resection may provide the best results in terms of local control, but carries a significant rate of postsurgical morbidity whose incidence and severity appears to be correlated to the extent of resection. The multidisciplinary management represents, according to current evidence, the best option for the treatment of spinal metastases. Noteworthy, according to the recent literature evidence, cases that once required radical surgical resection followed by low-dose conventional radiotherapy, can now be more effectively treated by minimally invasive spinal approaches followed by spine SRS with decreased morbidity, improved local control, and more durable pain control. This combination allows also to extend this standard of care to patients that would be too sick for an aggressive surgical treatment. Future efforts are needed to prospectively compare the effectiveness of these available treatment approaches, focusing primarily on outcomes of tumor control, treatment-related morbidity, and quality of life.